Iron Oxide Nanoparticles-Plant Insignia Synthesis with Favorable Biomedical Activities and Less Toxicity, in the "Era of the-Green": A Systematic Review - Nadia M. Hamdy; Amira A. Boseila; Ahmed Ramadan; Emad B. Basalious (MDPI AG, 2022)
In the era of favoring environment-friendly approaches for pharmaceutical synthesis, "green synthesis" is expanding. Green-based nanomedicine (NM), being less toxic and if having biomedical acceptable activities, thence, the chemical methods of synthesis are to be replaced by plants for reductive synthesis. Iron oxide nanoparticles (IONPs) exhibited remarkable anti-microbial and anti-cancer properties, besides being a drug delivery tool. However, owing to limitations related to the chemical synthetic method, plant-mediated green synthesis has been recognized as a promising alternative synthetic method. This systematic review (SR) is addressing plant-based IONPs green synthesis, characteristics, and toxicity studies as well as their potential biomedical applications. Furthermore, the plant-based green-synthesized IONPs in comparison to nanoparticles (NPs) synthesized via other conventional methods, characteristics, and efficacy or toxicity profiles would be mentioned (if available). Search strategy design utilized electronic databases including Science Direct, PubMed, and Google Scholar search. Selection criteria included recent clinical studies, available in the English language, published till PROSPERO registration. After screening articles obtained by first electronic database search, by title, abstract and applying the PICO criteria, the search results yielded a total of 453 articles. After further full text filtrations only 48 articles were included. In conclusion, the current SR emphasizes the perspective of the IONPs plant-mediated green synthesis advantage(s) when utilized in the biomedical pharmaceutical field, with less toxicity.